Comparing Conventional Physician-Led Education with VR Education for Pacemaker Implantation: A Randomized Study - Drozdova, Adela; Polokova, Karin; Jiravsky, Otakar; Jiravska Godula, Bogna; Chovancik, Jan; Ranic, Ivan; Jiravsky, Filip; Hecko, Jan; Sknouril, Libor (Healthcare (Basel, Switzerland), 2024)
INTRODUCTION: Education of patients prior to an invasive procedure is pivotal for good cooperation and knowledge retention. Virtual reality (VR) is a fast-developing technology that helps educate both medical professionals and patients. OBJECTIVE: To prove non-inferiority of VR education compared to conventional education in patients prior to the implantation of a permanent pacemaker (PPM). METHODS: 150 participants scheduled for an elective implantation of a PPM were enrolled in this prospective study and randomized into two groups: the VR group (n = 75) watched a 360° video about the procedure using the VR headset Oculus Meta Quest 2, while the conventional group (n = 75) was educated by a physician. Both groups filled out a questionnaire to assess the quality of education pre- and in-hospital, their knowledge of the procedure, and their subjective satisfaction. RESULTS: There was no significant difference in the quality of education. There was a non-significant trend towards higher educational scores in the VR group. The subgroup with worse scores was older than the groups with higher scores (82 vs. 76 years, p = 0.025). Anxiety was reduced in 92% of participants. CONCLUSION: VR proved to be non-inferior to conventional education. It helped to reduce anxiety and showed no adverse effects.
Keywords: health outcomes; pacemaker implantation; patient education; preoperative anxiety; medical technology in education; virtual reality